Interactive Serious Games: Communication and Play to Promote Intercultural Competence - Alexandra Schreiber; Dominik Wilhelm (Zeitschrift für Hochschulentwicklung, 2017)
SumMit is a project exploring theory and practice for implementing interactive serious games to be used to work on topics of intercultural competence in various formats. Conducted by graduate students, SumMit examines the dynamics which support players in their effort of leaving their primarily unconscious comfort zones of interaction and communication. Being designed for the use on tablet computers or smartphones, interaction takes place between players and combines elements of experiential learning with reflective debriefing units, thus leading to learning outcomes that can serve as starting point for discussion and further learning units.